Pengetahuan terhadap Sikap Ibu Hamil tentang Tanda Bahaya Kehamilan Trimester III - Zakaria, Rabia; Kadir, Raflin (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2021)
Indonesia is one of the developing countries in Southeast Asia with a high maternal mortality rate. One of the causes of the high maternal mortality rate is pregnancy complications that can appear through pregnancy danger signs. Danger signs of pregnancy are signs that indicate danger that can occur during pregnancy or the antenatal period, which if not detected can cause death. This study aims to determine the relationship between knowledge and attitudes of pregnant women about the danger signs of third-trimester pregnancy in one area of Central Indonesia. This study used an analytical survey method with approach cross-sectional. The sample in this study was 23 pregnant women. The sampling technique used was the consecutive sampling method. The consecutive sampling study was conducted in February - March 2020. The results showed a significant relationship between knowledge of the attitudes of pregnant women about the danger signs of third-trimester pregnancy. The conclusion in this study is that there is a significant relationship between knowledge of the attitudes of pregnant women about the danger signs of third-trimester pregnancy.